Development of Powerpoint-Based Interactive Learning Media - Arozatulo Bawamenewi; Zalukhu, Masdya; Nisirani Waruwu; Kaperius Daeli (EDUPEDIA Publisher, 2023)
The limited supporting media in the teaching and learning process causes the teaching and learning process to be less effective. To overcome this, it can be done by using power point-based interactive learning media on Indonesian language material. This research was conducted in class VII UPTD SMP Negeri 2 Gunungsitoli. The purpose of this study is to develop interactive power point-based learning media, to determine the level of student skills through the use of powerpoint learning media. The research method used is Borg and Gall research. Based on the research conducted and the formulation of the problem and research objectives, the authors conclude that the developed media is suitable for use in the Indonesian language learning process.